Histochemistry distribution of mucins and number of leucocytes in the lungs of postweaning pigs exposed to E. coli lipopolysaccharide (LPS) (2017)
ABSTRACT: Introduction. Currently, little is known about the effect of lipopolysaccharides (LPS) derived from E. coli on the number of goblet cells and the type of mucins secreted in the airways ofpiglets. Likewise, the differential distribution of these mucins and their relationship with the development of respiratory infections in the post-weaning period is not well understood. this information is useful to porcine production for the development of preventive and sanitary management strategies. Objective. This study aimed to evaluate the effect of the oral intake of E.coli LPS on the mucins distribution and the number of leukocytes in the lungs of early weaned piglets. Methods. 52 piglets weaned at 21 days were used. Animals were fed a basal diet with four levels of LPS (0.0, 0.3, 0.5, and 1.0μg /mg feed) for 10 days.Pigs were sequentially slaughtered on days 1, 5, 7, and 10 after weaning. Lung samples were taken for histochemical stainings (H-E, Alcian blue pH 1.0, 2.5, and PAS) in order to determine the amount and type of leukocytes as well as the number of goblet cells and their type of mucins produced. Mucins were classified according to their dyeing characteristicsas: acidic sulfated, non sulfated, and neutral, all by computerized image analysis.The statistical design used was a randomized blocks in a 4x4 factorial arrangement (four experimental diets and four days post-weaning). Results and discussion.Results showed a decrease in the number of goblet cells and neutral mucins in both bronchi and bronchioles in the control piglets, followed by a recovery minday 10 post-weaning. In groups with LPS such recovery was inhibited. In all study groups acidic mucins increased in bronchi on day five. There were no acidic mucins in their bronchioles. Moreover, the treatment with the higher concentration of LPS caused a decrease in the number of neutrophils on day 10 and had no effects on the amount of other leukocytes.Conclusions. LPS affects the recovery of goblet cells in the lung airway epithelium and decreases the number of neutrophils altering the innate immunity in early weaning.Consequently, it may facilitate the entry of pathogens and an allergen sensitization.